Knowledge and practice of colorectal cancer screening in an urban setting : cross-sectional survey of primary care physicians in government clinics in Malaysia. - Ooi, Chor Yau; Nik Sherina, Binti Hanafi; Liew, Su May (Singapore Medical Journal, 2019)
INTRODUCTION: Colorectal cancer (CRC) was the third most commonly diagnosed cancer worldwide in 2008 (1.23 million cases, 9.7%). CRC screening was shown to be effective in reducing 70% of CRC mortality. However, the screening rate for CRC remains poor.